Mechanotransduction in Liver Diseases - Kang, Ningling (Seminars in Liver Disease, 2020)
Chronic liver diseases, such as fibrosis and cancer, lead to a rigid or stiff liver because of perpetual activation of hepatic stellate cells or portal fibroblasts into matrix-producing myofibroblasts. Mechanical forces, as determined by the mechanical properties of extracellular matrix or pressure of circulating blood flow/shear stress, are sensed by mechanoreceptors at the plasma membrane and transmitted into a cell to impact cell function. This process is termed as mechanotransduction. This review includes basic knowledge regarding how external forces are sensed, amplified, and transmitted into the interior of a cell as far as the nucleus to regulate gene transcription and generate biological responses. It also reviews literatures to highlight the mechanisms by which mechanical forces in a normal or diseased liver influence the phenotype of hepatocytes, hepatic stellate cells, portal fibroblasts, and sinusoidal endothelial cells, and these cells in turn participate in the initiation and progression of liver diseases.
Keywords: integrins; focal adhesions; adherens junctions; cytoskeleton; epigenetics